Study on the Essential Variable ofWelding Procedure Specification (WPS) of Fillet Weld - Hamdan, Khaled (Universiti Teknologi PETRONAS, 2009)
The technique of welding with the right variable of welding procedure is important in determining the integrity of the weld. The objective of the project is to study the effect of the manipulated essential variable of Welding Procedure Specification of fillet weld on the structure which for this project is two plate of steel based on the established welding procedure specification. The challenge in this project is to perform the tests on the welding specimen to study the effect of manipulated essential variable of Welding Procedure Specification (WPS). The welding voltage of welding procedure was manipulated. Subsequently, mechanical test and non destructive test were done to analyze the fillet welds and the findings of the study were revealed. From the results, the higher voltage could decrease the brittleness of the weld and increase its ductility. It also can reduce the residual stress presence in the weld. Secondly, the higher voltage can make the weld have deeper fusion.